2022
DOI: 10.1101/2022.01.04.22268770
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Discordant SARS-CoV-2 PCR and Rapid Antigen Test Results When Infectious: A December 2021 Occupational Case Series

Abstract: The performance of Covid-19 diagnostic tests must continue to be reassessed with new variants of concern. The objective of this study was to describe the discordance in saliva SARS-CoV-2 PCR and nasal rapid antigen test results during the early infectious period. We identified a high-risk occupational case cohort of 30 individuals with daily testing during an Omicron outbreak in December 2021. Based on viral load and transmissions confirmed through epidemiological investigation, most Omicron cases were infecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
97
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(113 citation statements)
references
References 4 publications
13
97
3
Order By: Relevance
“…On the other hand, in symptomatic non-hospitalized patients in South Africa, saliva samples detected Omicron more often than mid-turbinate swabs (100% vs. 86% respectively) 8 which was opposite from the performance reported for previously circulating variants. Similarly, in a pre-print non-peer reviewed publication of a small subset of individuals in a high-risk occupational case cohort, the viral load in saliva specimens peaked 1 to 2 days prior to those observed with nasal swab collections 23 . These early data suggest there may be a different tissue tropism for the Omicron variant compared to prior circulating lineages of SARS-CoV-2 7 .…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…On the other hand, in symptomatic non-hospitalized patients in South Africa, saliva samples detected Omicron more often than mid-turbinate swabs (100% vs. 86% respectively) 8 which was opposite from the performance reported for previously circulating variants. Similarly, in a pre-print non-peer reviewed publication of a small subset of individuals in a high-risk occupational case cohort, the viral load in saliva specimens peaked 1 to 2 days prior to those observed with nasal swab collections 23 . These early data suggest there may be a different tissue tropism for the Omicron variant compared to prior circulating lineages of SARS-CoV-2 7 .…”
Section: Discussionmentioning
confidence: 90%
“…Similarly, in a pre-print non-peer reviewed publication of a small subset of individuals in a high-risk occupational case cohort, the viral load in saliva specimens peaked 1 to 2 days prior to those observed with nasal swab collections 23 . These early data suggest there may be a different tissue tropism for the Omicron variant compared to prior circulating lineages of SARS-CoV-2 7 .…”
Section: Discussionmentioning
confidence: 90%
“…While we chose a Ct value cutoff of 30 as a proxy for infectiousness [13][14][15][16][17] , this threshold should not be considered a perfect predictor of infectiousness. Second, the Ct values reported here are from samples that each combined anterior nares and oropharyngeal swabs and were performed on the Roche Cobas platform; results may differ by anatomical site and by PCR platform [24][25][26][27] . Third, this relatively small sample set was obtained in a population that is not representative of the general population.…”
Section: Discussionmentioning
confidence: 99%
“…This is because the clinical sensitivity of an assay is influenced by factors inherent to the virus as well as host factors such as pre-existing immunity. For instance, Abramson et al reported the propensity for the BinaxNOW™ and the Quidel Quickvue™ LFIAs to be falsely negative early in infection despite very high viral loads detected concomitantly from saliva samples 11 . Antigen detection from nasal swab samples eventually turned positive several days after symptom onset, suggesting that viral replication may initially localize to the oropharynx prior to transitioning to the nasopharynx.…”
Section: Discussionmentioning
confidence: 99%